Penerapan Terapi Brain Gym Untuk Perubahan Fungsi Kognitif Pada Pasien Skizofrenia Di Rsjd Dr. Arif Zainuddin Surakarta - Tania Anugerah Siwi Nur Aini; Sitti Rahma Soleman; Luluk Purnomo (An-Najat, 2024)
Background: Schizophrenia is one of the mental disorders that has a high global prevalence where the impact of these symptoms can cause a decrease in cognitive function, There are various kinds of therapies that can be done to improve cognitive function, one of these therapies is Brain Gym where this therapy is useful for stimulating the brain so that it can maintain cognitive abilities, Objective: To determine the results of the application of Brain gym therapy for changes in cognitive function in schizophrenia patients. Methods: The method used in this application is descriptive with a pre-test post-test case study application design on 2 respondents, the application instrument is the C-SARS questionnaire observation sheet. Results: Before being given Brain gym therapy Mr. E and Mr. A were in the moderate category with scores of 19 and 17. After being given Brain gym therapy Mr. E and Mr. A are in the mild category with scores of 9 and 8. Conclusion: There was an increase in cognitive function in Mr. E. A and Mr. E from initially in the moderate category to the mild category after being given brain gym therapy